Hypernasality in the Speech of Iraqi Children with Cleft Palate: A Generic Feature - Geometry Based Model - احمد عبد الستار السامر, محمد (Al-Adab Journal, 2018)
This paper is concerned with a generic feature geometry based model for phonological disorder description of hypernasality routed in the voice profiles of an Iraqi child (aged 7 years) with a cleft palate. It primarily explores the applicability of this model to the resonance hypernasalization deficit elicited in this single-case study. The preliminary findings of the treatise reveal that the subject under study has a limited linguistic competence, due to the dysfunction of the velopharyngeal valve, caused by the cleft palatology, which negatively militates his communicative skills. The most common resonance distortions resulted from this dysfunction are glottalization (25.95%), consonantal hypernasality(23.40%),vocalic hypernasality (21.019%), pharyngealisation (8.75%), labialization (7.48%), lateralization (7%), elision (4.93%), initial cluster simplification (1.11%), metathesis and vocalic shortening (0.15%), equally. Corpus analysis via manner association scheme (within the framework of Autosegmental Phonology) divulges that this model is significantly applicable to hypernasalized vowels. However, this autosegmental model fails to capture the manner co-attachment association in certain cases of vocalic and consonantal hypernasality pointing in the direction of harmonic nasality.